Metaphorical conceptualization of gender in terminology: a corpus-based study - Sobirova, Zarxala Boltakulovna (The Lingua Spectrum, 2026)
This study investigates the metaphorical conceptualization of gender terminology in British and American English through a corpus-based comparative analysis. Drawing on Conceptual Metaphor Theory (Lakoff & Johnson, 1980) and critical discourse perspectives, the research examines how gender-related lexical units are structured through systematic metaphorical mappings. Data were extracted from the British National Corpus and the Corpus of Contemporary American English, two large and balanced corpora representing British and American English respectively. The study focuses on key gender-related terms, including gender, woman/women, man/men, masculinity, femininity, and feminism. Quantitative analyses were conducted using normalized frequency counts, collocation analysis within a ±5-word window, Mutual Information (MI) scores, log-likelihood testing, and keyness analysis. Metaphorical expressions were identified using the MIPVU procedure and classified into broader source domains. The metaphorical patterns identified in this study have important implications for understanding how language shapes gender ideology. When masculinity is recurrently mapped onto POWER and COMPETITION, and femininity onto CARE and VULNERABILITY, discourse contributes to the reproduction of asymmetrical agency. Even in progressive contexts, conflict-based metaphors may inadvertently reinforce binary oppositions.